Cystic neoplasms of pancreas: Importance of differential diagnosis [Pankreasin kistik tümörleri: Ayinci taninin önemi] - (:unkn) unknown (Turkish Surgical Society, 2008)
Cystic neoplasms of pancreas consist approximately 15-20%of all cystic lesions. The most prominent tumors are serous, mucinous and intraductal papillary mucinous ones. In the absence of pancreatitis history, all of the cystic pancreatic lesions must be accepted as neoplasms until otherwise proven. Diagnostic process is difficult and has an outmost importance for choosing the treatment modality. Whereas serous cystic tumors are generally of benign character, mucinous ones are either premalignant or malignant. Asymptomatic serous cystic neoplasms may be followed without treatment. Mucinous cystic and intraductal papillary mucinous neoplasms should be resected. The best treatment for these tumors is anatomic resection. The prognosis is guite good if there is no tumor invasion. Invasive tumors have a worse prognosis and may be followed with CT and/or endoscopic ultrasonography.
Keywords: Cystic neoplasm; Intaductal papillary; Mucinous; Pancreas; Serous